Implementasi Keselamatan dan Keamanan Kapal Kapal yang Berlabuh (Drop Anchor) di Wilayah Perairan Batam - Sasongko, Awang (Universitas Internasional Batam, 2019)
The main purpose of this research is to understand the role of Syahbandar in the execution of shipping activities in sea freight in territorial waters according to